2008
DOI: 10.1017/s0265021508004717
|View full text |Cite
|
Sign up to set email alerts
|

The neuromuscular effects of 0.6 mg kg−1 rocuronium in elderly and young adults with or without renal failure*

Abstract: The neuromuscular effects of 0.6 mg kg(-1) rocuronium under propofol anaesthesia were markedly prolonged in young and elderly renal failure patients compared to patients with normal renal function, and also in elderly patients with normal renal function compared with young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…Similar cases have been seen in the literature, where even smaller doses of rocuronium (0.6 mg/kg) resulted in NMB of over 10 h 91012…”
Section: Discussionsupporting
confidence: 86%
“…Similar cases have been seen in the literature, where even smaller doses of rocuronium (0.6 mg/kg) resulted in NMB of over 10 h 91012…”
Section: Discussionsupporting
confidence: 86%
“…Rocuronium is not dependent on renal blood flow for its major route of excretion, but is taken up by the liver and excreted into the bile in high concentrations [9]. Although hepatic uptake and biliary elimination are thought to be the main routes of elimination for rocuronium, it seems that renal failure can have a marked effect on rocuronium pharmacokinetics and pharmacodynamics, although not consistently so [16][17][18]. In patients with no or minimum renal function, the clinical duration and recovery time of rocuronium 0.6 mg/kg increased significantly [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that about 10% of the IV dose of rocuronium was excreted in urine [17,19]. Kocabas et al [20] reported that the clearance of rocuronium was reduced by 39% in patients suffering from renal failure compared with controls, with 84% increase in the mean residence time, whereas the volume of distribution was unaffected by renal failure. Therefore, the duration of action of rocuronium can be expected to be prolonged, as it undergoes organ-dependent elimination [20].…”
Section: Discussionmentioning
confidence: 99%
“…Kocabas et al [20] reported that the clearance of rocuronium was reduced by 39% in patients suffering from renal failure compared with controls, with 84% increase in the mean residence time, whereas the volume of distribution was unaffected by renal failure. Therefore, the duration of action of rocuronium can be expected to be prolonged, as it undergoes organ-dependent elimination [20]. Proost et al [3] demonstrated that rocuronium is taken up by the liver and excreted into the bile in very high concentration [3].…”
Section: Discussionmentioning
confidence: 99%